Modulation of Vasomotive Activity in Rabbit External Ophthalmic Artery by Neuropeptides - Esmeralda Sofia Costa Delgado; Carlos Marques-Neves; Maria Isabel Sousa Rocha; José Paulo Pacheco Sales-Luís; Luís Filipe Silva-Carvalho (Journal of Ophthalmology)
Purpose. To investigate the vasomotive activity upon the external ophthalmic artery of vasointestinal peptide (VIP) and neuropeptide Y (NPY) using a previously developed model. Methods. Isolated rabbit eyes (n=12) were perfused in situ with tyrode through the external ophthalmic artery. Effects of intra-arterial injections of NPY 200 μg/ml (Group A; n=6) and VIP 200 μg/ml (Group B; n=6) on the recorded pressure were obtained. For statistical analysis, Student's paired t-test and Fast Fourier Transform were used. Results. Spontaneous oscillations were observed before any drug administration in the 12 rabbit models. NPY produced an increase in total vascular resistance and a higher frequency and amplitude of oscillations, while VIP evoked the opposite effects. Conclusions. This study provides evidence of vasomotion in basal conditions in rabbit external ophthalmic artery. Concerning drug effects, NPY increased arterial resistance and enhanced vasomotion while VIP produced opposite effects which demonstrates their profound influence in arterial vasomotion.